Labor market regulation and informality - Luiz Mário Brotherhood; Daniel da Mata; Nezih Guner; Philipp Kircher; Cézar Santos (Inter-American Development Bank (IDB), 2024)
This paper investigates informal employment in Brazil's highly regulated labor market, focusing on the intensive margin of informality within formal firms. Using a comprehensive dataset of labor audits conducted from 1997 to 2012, we find that formal firms caught with informal workers face sustained slower growth. Informal workers are found across firms of all sizes, and their characteristics closely resemble those of formal employees. Building on these empirical findings, we develop a dynamic general equilibrium model where firms balance the flexibility of informality against potential costs. Our framework can be used to explore government policy implications and to examine the impact of audit strategies on informality, output, and workers welfare.
Keywords: H2; J1; J2; L1; 330; Informality; Labor market regulation; Firm dynamics; Developingcountries